Intracranial aneurysm and subarachnoid hemorrhage in a 4-years-old patient - Flávio Ramalho Romero1; Rodolfo Brum Vieira2 (Global Journal of Rare Diseases - Peertechz Publications, 2019)
Pediatric intracranial aneurysm (PIA) is a rare condition, accounting 7% of all intracranial aneurysms. A slight male predominance is observed (two to one) and 25% of lesions are in posterior circulation. PIA should be considered in children with sudden headache and unexplained loss of consciousness. Treatment is challenging and technically demanding comparing with adult cases. Here we present a case of 4-years-old girl with sudden headache and seizures, with CT-scan showing subarachnoid hemorrhage and angio-CT with anterior communicating complex aneurysm. Our choice was microsurgical clipping and outcome was very good [1-5].